Recombinant allergen-specific antibody fragments: tools for diagnosis, prevention and therapy of type I allergy. - Valenta, R; Flicker, S; Eibensteiner, P; Steinberger, P; Laffer, S; Dolecek, C; Kraft, D (1997)
Type I allergy represents a hypersensitivity occurring in almost 20% of the population that is based on the recognition of innocuous airborn antigens (pollen, mite, mould and pet allergens) by specific immunoglobulin E. Allergic symptoms (e.g. allergic rhinitis, conjunctivitis, asthma) are caused by the release of biological mediators from effector-cells after allergen-induced crosslink of receptor-bound IgE. Here we discuss strategies to obtain recombinant allergen-specific antibody fragments (Fabs) from mouse and human cell lines as well as directly from allergic patients lymphocytes via the combinatorial library technology. It is suggested to use recombinant allergen-specific Fabs for the standardization of allergen extracts currently used for diagnosis and treatment, to determine allergen contents in allergen sources and the environment to allow preventive measures and to use allergen-specific Fabs as therapeutic tools to interfere with the allergen-IgE interaction. The latter appears possible because IgE represents the least abundant class of immunoglobulins and there is increasing evidence for a limited diversity among allergens and their B-cell epitopes. Moreover, allergic effector reactions are mostly confined to accessible target organs so that a local application of competing Fabs prior to allergen exposure might represent a feasible therapeutic approach.